2009
DOI: 10.1007/s12630-008-9024-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided block of the brachial plexus at the humeral canal

Abstract: Purpose Conduction block of the brachial plexus block at the humeral canal, as described by Dupre, has certain clinical indications. The aim of this preliminary study was to assess the feasibility of this technique under ultrasound guidance. Methods After ultrasound evaluation of the brachial plexus at the humeral canal in 61 adult volunteers, we performed ultrasound-guided blocks in another 20 adult patients. A linear 38 mm probe, 13-6 MHz, and a 50-mm insulated block needle were used to guide injection of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…By blocking peripheral nerves at the level of low-median 1/3 and upper-median 1/3 of the arm, where they are relative thin, allowed easy infiltration of local anesthetics. Therefore, the onset time of the sensory block was shorter and consistent with the work of Guntz [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By blocking peripheral nerves at the level of low-median 1/3 and upper-median 1/3 of the arm, where they are relative thin, allowed easy infiltration of local anesthetics. Therefore, the onset time of the sensory block was shorter and consistent with the work of Guntz [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, motor function at the elbow was still impaired. Guntz et al [ 9 ] reported that ultrasound-guided block of the brachial plexus at the humeral canal could allow the patient to recover the flexion of the forearm while providing effective post-operative analgesia. However in our study, patients could retain flexion and extension of the elbow with effective post-operative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasonography to facilitate brachial plexus blocks with local anesthetic has been described previously in other species (Guntz et al. 2009; Campoy et al.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasonography to facilitate brachial plexus blocks with local anesthetic has been described previously in other species (Guntz et al 2009;Campoy et al 2010), and has been shown to improve the efficacy of the block because the operator can visualize the location of the needle relative to the nerves and the spread of local anesthetic around the nerves; this reduces complications such as intravascular and intrathoracic injections of local anesthetic (Pandin et al 2006). The goal of this project was to deposit the lidocaine as close as possible to the brachial plexus, without causing nerve damage, and anesthetize the wing.…”
Section: Figurementioning
confidence: 99%
“…In addition to analyzing the site of a nerve trauma, real-time US imaging offers the advantage over alternative imaging techniques by allowing visualization of anatomical nerve structures, while simultaneously performing invasive procedures, such as the placement of needles and stimulating electrodes (Dufour et al, 2008;Guntz et al, 2009;Harmon and Hearty, 2007;Huntoon et al, 2008;Koscielniak-Nielsen et al, 2008). Thus, US imaging of peripheral nerves is increasingly used clinically for a wide range of applications and has great potential for additional applications * Tel.…”
Section: Introductionmentioning
confidence: 99%